How the Bible became a book the textualization of ancient Israel - Schniedewind, William M. (Cambridge, U.K. ; New York : Cambridge University Press, 2004)
For the past two-hundred years Biblical scholars have usually assumed that the Hebrew Bible was mostly written and edited in the Persian and Hellenistic periods (5th-2nd centuries B.C.E.). Recent archaeological evidence and insights from linguistic anthropology, however, point to the earlier era of the late Iron Age (8th-6th centuries B.C.E.) as the formative period for the writing of biblical literature. This book combines recent archaeological discoveries in the Middle East with insights from the history of writing to address how the Bible first came to be written down and then became sacred Scripture. It provides insight into why these texts came to have authority as Scripture and explores why Ancient Israel, an oral culture, began to write literature. It describes an emerging literate society in ancient Israel challenging the assertion that literacy first arose in Greece during the fifth century B.C.E.--From publisher description.
How the Bible became a book -- The numinous power of writing -- Writing and the state -- Writing in early Israel -- Hezekiah and the beginning of Biblical literature -- Josiah and the text revolution -- How the Torah became a text -- Writing in exile -- Scripture in the shadow of the Temple.
Includes bibliographical references (p. 215-216) and index.
Description based on print version record.
Keywords: Bible -- History; Bible -- Histoire; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference; Oude Testament; Mondelinge overlevering; Schriftcultuur; Canon; Electronic books